Markups, inequality and monetary‐fiscal policies. (18th February 2022) - Chu, Shiou‐Yen
Abstract: This paper reexamines the cyclical behaviors of price markup, profits, and labor share when responding to monetary and fiscal policy shocks in a two‐agent, two‐branch, and two‐sector model. We show that this framework is able to generate procyclical price markup and profits, and countercyclical labor share conditional on expansionary policy shocks. These results are in line with empirical evidences but at odds with the prediction of canonical New Keynesian models. As the share of nondurables in total production decreases, the results reverse. This finding implies expansionary monetary and fiscal policies widen the income inequality between Ricardian households and collateral‐constrained households.